A potencialidade do trabalho: uma via para o desenvolvimento sociocultural - Giacomo, Marcos Flud (2015)
We live in a work society. In the course of accumulated jobs in our curricula vitae we daily share with others in a rich laboratory of experiences, not only professionals but mainly personal. In addition to technical knowledge, we collect socio-cultural experiences. We shape our character and build our personal values. In the name of productivity we constantly challenge ethics and threaten the environment. The contemporary work presents peculiarities dating back to the industrial revolution. Its format is not contributing to the development of the human being, increasingly fragmented in its specializations. Fears and insecurities prevail in the workplace of organizations, causing widespread stress in the search for short-term goals, performance and profits. We learn, build, produce, while workers. We live the joys, sorrows, accomplishments, frustrations, emotions, fears, vanities in the human role, inseparable from the professional one. Growing consciousness from ourselves and others, from our accomplishments and the things that discourage us. We mature. This equation appears to lack from a variable that makes our relationship with the work positive. While experiencing changes on the route of the economic model, the purpose presents itself as a possible via to the social-cultural regeneration